Chemical environment of water molecules adsorbed on the anatase surface: quantum chemical study - O. V. Smirnova; A. G. Grebenyuk; V. V. Lobanov (Хімія, фізика та технологія поверхні)
Theoretical studies of the interactions of an oxygen molecule with the surface of a solid phase are of great importance for understanding the mechanisms of reactions involving oxygen on a solid surface. In this work, the spatial and electronic structure of oxygen defects and nitrogen impurity centers of the anatase surface and their manifestation in water adsorption are investigated. The anatase surface was simulated for by clusters of the composition Ti14H22O39 (defect-free face (001)), Ti14H22O38 (surface with oxygen vacancy), and Ti14H22N2O36 (surface with both oxygen vacancy and incorporated nitrogen), terminated with boundary hydrogen atoms.